If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9 = 18 + -5x Reorder the terms: -9 + 4x = 18 + -5x Solving -9 + 4x = 18 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -9 + 4x + 5x = 18 + -5x + 5x Combine like terms: 4x + 5x = 9x -9 + 9x = 18 + -5x + 5x Combine like terms: -5x + 5x = 0 -9 + 9x = 18 + 0 -9 + 9x = 18 Add '9' to each side of the equation. -9 + 9 + 9x = 18 + 9 Combine like terms: -9 + 9 = 0 0 + 9x = 18 + 9 9x = 18 + 9 Combine like terms: 18 + 9 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| (2a^5b)^2/24b^6 | | Tanx+2=1.9 | | 7s+4q-5s+3q= | | a(19)=12-2n | | X^2-12x+84=12y | | 2r-4=5(r+7) | | y=3x^2-36x-100 | | 8(6+7)+x=7x | | 2(27-b)=100-4b+6(s-b) | | 5x-13=4x-2 | | 5x-13=4x-2•/.2 | | 2/3(2-x)-1/2(2x+5)=5/6(-x-3) | | Y^10/Y^6 | | 22.75=20c+5.75 | | (26n-6)=13n | | v^7-v^5=c | | v^7-v^5-c=0 | | 7x^2+20=6 | | 8m+2=16m+2 | | 12/2(3)*2 | | 12/2(3)x2 | | x+2x+3x=50 | | 4-3ln(x+5)=1 | | 2x+40.3=-6x-40.3 | | b+6=26 | | f(x+h)=2x^2+5x+8 | | 8x^2+27x-63=0 | | 0=-16t^2-200 | | 3/p=9/7 | | 3k^2+30k=0 | | 9x^2-7x-9=0 | | e^2x-4+3=2 |